Comparison of the Superagonist Complex, ALT-803, to IL15 as Cancer Immunotherapeutics in Animal Models - Rhode, Peter R; Egan, Jack O; Xu, Wenxin; Hong, Hao; Webb, Gabriela M; Chen, Xiaoyue; Liu, Bai; Zhu, Xiaoyun; Wen, Jinghai; You, Lijing; Kong, Lin; Edwards, Ana C; et al. (Cancer immunology research, 2016)
IL15, a potent stimulant of CD8(+) T cells and natural killer (NK) cells, is a promising cancer immunotherapeutic. ALT-803 is a complex of an IL15 superagonist mutant and a dimeric IL15 receptor αSu/Fc fusion protein that was found to exhibit enhanced biologic activity in vivo, with a substantially longer serum half-life than recombinant IL15. A single intravenous dose of ALT-803, but not IL15, eliminated well-established tumors and prolonged survival of mice bearing multiple myeloma. In this study, we extended these findings to demonstrate the superior antitumor activity of ALT-803 over IL15 in mice bearing subcutaneous B16F10 melanoma tumors and CT26 colon carcinoma metastases. Tissue biodistribution studies in mice also showed much greater retention of ALT-803 in the lymphoid organs compared with IL15, consistent with its highly potent immunostimulatory and antitumor activities in vivo. Weekly dosing with 1 mg/kg ALT-803 in C57BL/6 mice was well tolerated, yet capable of increasing peripheral blood lymphocyte, neutrophil, and monocyte counts by >8-fold. ALT-803 dose-dependent stimulation of immune cell infiltration into the lymphoid organs was also observed. Similarly, cynomolgus monkeys treated weekly with ALT-803 showed dose-dependent increases of peripheral blood lymphocyte counts, including NK, CD4(+), and CD8(+) memory T-cell subsets. In vitro studies demonstrated ALT-803-mediated stimulation of mouse and human immune cell proliferation and IFNγ production without inducing a broad-based release of other proinflammatory cytokines (i.e., cytokine storm). Based on these results, a weekly dosing regimen of ALT-803 has been implemented in multiple clinical studies to evaluate the dose required for effective immune cell stimulation in humans.